Access to N-Alkylpyrazin-2-ones via C–O to C–N Rearrangement of Pyrazinyl Ethers - Dacho, Vladimír; Nitrayová, Dária; Šoral, Michal; Machyňáková, Andrea; Moncoľ, Ján; Szolcsányi, Peter (SynOpen, 2019)
The reaction of tosylated 2-alkoxypyrazines with potassium halides led to the unexpected formation of N-alkylated pyrazinones. Such rare example of substitutive C–O → C–N rearrangement on pyrazines was then scrutinised by using various nucleophiles to afford the respective products in moderate to good yields. This method provides a direct access to N-alkylated-1H-pyrazin-2-ones. The formation of the rearranged products is conveniently and reliably determined by characteristic NMR shifts of their heteroaromatic protons.
Keywords: pyrazinones; rearrangement; SN reaction; NMR spectroscopy; X-ray crystal structure analysis